XRF study on the gilding technique of the fresco 'Crocifissione con Santi' by Beato Angelico in the San Marco monastery in Florence. (14th July 2015) - Mazzinghi, A.; Giuntini, L.; Gelli, N.; Ruberto, C.
Abstract : This study focused on the gildings of a famous Italian fresco, the Crocifissione con Santi by Beato Angelico, exploiting the XRF spectrometer developed at the LABEC laboratory. This can be considered the first scientific study on the gilding technique on frescoes of Beato Angelico. In order to characterise the original gilding technique and identify restored parts, more than 30 points were analysed in different areas of the wall painting, mostly in halos and decorations. In particular, the main goal was to verify whether Beato Angelico used the composite tin–gold foil, the most common gilding technique during the Italian Renaissance. This study allowed discriminating the original from the restored gildings, and to characterise the layers in both cases, by means of iron Kα/Kβ ratio. Copyright © 2015 John Wiley & Sons, Ltd.